The presence of a Latin American psychological line in the Anglo-Saxon academic context: the Psychology of Liberation in Scopus (2002-2015) - Luiz Pinto, Adilson; Paredes, Hector Alejandro; Sousa Netto, Manoel Camilo (AWARI, 2020)
Liberation psychology is a theory born in Latin America. This article studies the psychology of liberation in the Scopus database, with the aim of deepening historically on the subject and identify their visibility among Anglos-Saxons scientists. The study is a temporal analysis (2002-2015), in order to know their history, the key players in its creation, authors' greater impact on publications and major scientific journals. Also, it conducted an analysis of production according to the authorities, publications, terminologies, and citations. This study uses as tools data analysis Programs (Createpajek) and display of information (Netdraw). The main results in a universe of 55 papers were: 9 main authors; 3 elite journals that publish more than 41% of the articles; a universe 7 keywords that control the law of the least effort, and the replication of the most cited journals.